57.1k views
5 votes
Use substitution to solve this system of linear equations.

{(10x-2y=4),(3x-6y=12):}
A(0,2)
B(0,-2)
C(0,-4)
D(0,-6)

1 Answer

0 votes

Answer:

B

Explanation:

10x - 2y = 4 ( subtract 10x from both sides )

- 2y = 4 - 10x ( divide through by - 2 )

y = - 2 + 5x → (1)

3x - 6y = 12 → (2)

substitute y = - 2 + 5x into (2)

3x - 6(- 2 + 5x) = 12 ← distribute parenthesis on left side and simplify

3x + 12 - 30x = 12

- 27x + 12 = 12 ( subtract 12 from both sides )

- 27x = 0 ⇒ x = 0

substitute x = 0 into (1)

y = - 2 + 5(0) = - 2 + 0 = - 2

solution is (0, - 2 )

User Zpangwin
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.